A method for quantitatively controlling preparation of two-dimensional Pd nanosheets with controllable defects based on template state parameters

CN123000000APending Publication Date: 2026-10-30LINGNAN NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611219713.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-12
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0007]针对现有表面活性剂模板法依赖宏观浓度试错、无法定量控制胶束微观状态,从而导致合成机理不清、可预测性差、工艺窗口模糊及产物重现性低的核心缺陷,本申请提供了一种基于模板状态参数定量控制制备缺陷可控二维Pd纳米片的方法

Benefits of technology

[0042](1)本申请提供了定量化、标准化的胶束模板表征与合成控制流程:通过引入标准化的稳态荧光猝灭测绘步骤,将传统上不可见的胶束动态行为转化为可精确测量的Nagg值,并使其成为连接合成条件与产物形貌的唯一量化桥梁,彻底解决了“认知黑箱”问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123000000A_ABST
    Figure CN123000000A_ABST
Patent Text Reader

Abstract

The application discloses a method for preparing two-dimensional Pd nanosheets with controllable defects based on template state parameters, and belongs to the technical field of predictable synthesis and precise manufacturing of nanomaterials. The application provides a "quantitative micelle engineering" paradigm: a steady-state fluorescence quenching method is used to determine the micelle aggregation number N agg in the synthesis system, standardization mapping is performed, a quantitative relationship map of the CTAB concentration and N agg is established, N agg is correlated with the product morphology through systematic synthesis experiments, and the effective design interval 69-81 of N agg capable of stably guiding the target two-dimensional nanosheet structure is scientifically defined; the interval is used as the only control scale, a CTAB concentration process window is reversely determined, and synthesis is performed. The application changes the dynamic micelle from a "black box" into a quantitatively controllable parameter, realizes high-reproducibility and predictable rational preparation of the morphology and defect structure of two-dimensional palladium nanosheets, and the obtained product has excellent performance in electrocatalysis.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of predictable synthesis and precision manufacturing technology of nanomaterials, and in particular relates to a method for preparing two-dimensional Pd nanosheets with controllable defects based on the quantitative control of template state parameters. Background Technology

[0002] In the field of electrocatalysis, the development of highly active and stable noble metal nanocatalysts is key to promoting the development of clean energy technologies such as fuel cells and water electrolysis. Among them, two-dimensional Pd nanosheets have become a highly promising material reserve due to their unique electronic structure, high proportion of active crystal facet exposure, and tunable defect structure. Studies have shown that by precisely designing Pd nanostructures, their performance in important electrocatalytic conversions such as alcohol oxidation and hydrogen evolution reaction can be significantly improved, showing broad prospects for energy and chemical applications (see reference: Wang C, Xu H, Shang HY, et al. Ir-doped Pd nanosheetassemblies as bifunctional electrocatalysts for advanced hydrogen evolution reaction and liquid fuel electrocatalysis[J]. Inorganic Chemistry, 2020, 59(5):3321-3329.).

[0003] To achieve controllable preparation, the surfactant soft template method is a common strategy (see: Lim HS, Kani K, Henzie J, et al. A universal approach for the synthesis of mesoporous gold, palladium and platinum films for applications in electrocatalysis[J]. Nature Protocols, 2020, 15(9):2980-3008.). However, this field has long been constrained by an empirical and semi-quantitative traditional research paradigm. Researchers usually simplify the dynamic and complex micellar self-assembly system into a static "capping agent" or "stabilizer". The core design logic is to repeatedly screen the macroscopic concentration, type, ratio and other "formulation parameters" of surfactants through a large number of experiments in order to achieve a general guidance on the morphology of nanocrystals (see: Song TX, Gao F, Guo SY, et al. A review of the role and mechanism of surfactants in the morphology control of metal nanoparticles[J]. Nanoscale, 2021, 13(7):3895-3910.). This "trial and error" approach leads to a synthesis process that heavily relies on personal experience and lacks predictable, rational design principles.

[0004] This paradigm flaw is particularly evident in the soft-template synthesis of noble metal nanosheets. Taking the hexadecyltrimethylammonium bromide (CTAB) template method for synthesizing Pd nanosheets as an example, existing studies have generally focused on optimizing macroscopic variables such as CTAB concentration and precursor ratio, but the core mechanism of action—the real-time and quantitative microscopic state of the micelle template itself—has remained untouched and uncharacterized (see references: Yang M, Pang MY, Chen JY, et al. Surfactant-assisted synthesis of palladium nanosheets and nanochains for the electrooxidation of ethanol[J].ACS Applied Materials & Interfaces, 2021, 13(8): 9830-9837. and Cui ZL, Bai XF. Ultrasonic-assisted synthesis of two dimensional coral-like Pd nanosheets supported on reduced graphene oxide for enhanced electrocatalytic performance[J]. Ultrasonics Sonochemistry, 2021, 70: 105309.). Even in successful cases, the design logic has never transcended trial and error. For example, in the research on the preparation of two-dimensional mesoporous materials using block copolymer self-assembly, the success still largely depends on the empirical exploration of specific solvent composition, temperature and other conditions, rather than using the quantitative state parameters of micelles as a direct design basis for predicting and controlling the final structure (see reference: Alvarez-Fernandez A, Maiz J, Faustini M, et al. Mesoporous thin film architectures: addressing material demands through molecular self-assembly[J]. Accounts of Materials Research,2025,6(3):123-135.).Similarly, other strategies that regulate the growth mode of nanocrystals by introducing additional end-capping agents (such as selenium) still revolve around trial and error of macroscopic variables such as additive types and ratios, and also fail to touch and quantify the core dynamic state of the template (see reference: Hu C, Zhang YY, Ren RJ, et al. Aseleniium-mediated layer-by-layer synthetic strategy for multilayered multicomponent nanocrystals[J]. Nature Synthesis,2024,3(10):1299-1309.).

[0005] Ultimately, existing technologies all expose a fundamental flaw: treating the "template state" as an unmeasurable and uncontrollable "black box." This directly leads to three interconnected and serious consequences: 1. Cognitive black box and lack of mechanism: Existing technologies are completely unable to answer the question of what microscopic state (e.g., size, shape, degree of order) the micelle template is in at the so-called "effective concentration." This is due to a complete lack of understanding of core state parameters (e.g., micelle aggregation number N). agg (1) Real-time measurement and quantification of the synthesis mechanism are lacking, as the mechanism remains largely in a state of vague qualitative speculation, making it impossible to establish a universal structure-activity relationship. 2. Design logic gaps and predictability failures: Due to the aforementioned cognitive black box, existing technologies are fundamentally incapable of establishing a quantitative bridge between "synthesis conditions → template state → final product morphology." Each successful formulation becomes an isolated "data point." When the system or target changes, previous experience provides almost no effective guidance, forcing R&D to restart a time-consuming trial-and-error cycle. 3. Ambiguous process windows and reproducibility dilemmas: From an industrialization perspective, the fragility of existing methods is particularly prominent. They place all hope for process success on a set of isolated, precise "formulation parameters," completely failing to define, in principle, a tolerant "process state window" capable of stably producing the target product. This leads to an abnormally sensitive production process to minute fluctuations, poor batch-to-batch reproducibility, and a lack of scientific basis for the transformation of laboratory results into large-scale production.

[0006] Therefore, there is an urgent need in this field for a breakthrough solution that can open the "template state" black box and enable rational design and predictable synthesis of nanocrystal morphology. Summary of the Invention

[0007] To address the core shortcomings of existing surfactant template methods, which rely on macroscopic concentration trial and error and cannot quantitatively control the microscopic state of micelles, resulting in unclear synthesis mechanisms, poor predictability, ambiguous process windows, and low product reproducibility, this application provides a method for preparing defect-controllable two-dimensional Pd nanosheets based on the quantitative control of template state parameters. Specifically, the key problem this application aims to solve is: how to use a standardized quantitative mapping method to determine the intrinsic state parameter of dynamic micelles—the aggregation number (N)... agg — This is established as the direct control target for synthesis, thereby replacing the dependence on fuzzy concentration parameters, and ultimately achieving highly reproducible and predictable rational preparation of the morphology and structure of two-dimensional palladium nanosheets.

[0008] To achieve the above-mentioned objectives, this application provides the following technical solution:

[0009] On the one hand, this application provides a method for quantitatively preparing defect-controllable two-dimensional Pd nanosheets based on template state parameters, comprising the following steps:

[0010] (1) The aggregation number N of micelles formed by different concentrations of surfactant in the synthesis reaction system was determined by steady-state fluorescence quenching method. agg Measurements were performed, and a graph was plotted showing the relationship between surfactant concentration and micelle aggregation number N. agg Quantitative relationship graph;

[0011] (2) Based on the quantitative relationship spectrum drawn in step (1), select at least 5 characteristic concentration points covering the full concentration range, and synthesize a series of Pd nanomaterial samples in parallel while keeping all other synthesis conditions consistent. Quantitatively characterize the morphology of the obtained samples and determine the N corresponding to each sample. agg The value is correlated with its morphological quantification index, and N is plotted. agg - Morphology index relationship curve, based on which the N-type nanomaterials capable of stably synthesizing two-dimensional Pd nanosheets with the target morphology are determined. agg Effective design range;

[0012] (3) N determined in step (2) agg The effective design interval is the only control target. Based on the quantitative relationship graph drawn in step (1), reverse search and calculation are performed to determine the N that can be controlled in the system. agg The surfactant concentration range falling within the effective design range is used for the ultrasonic radiation chemical synthesis of Pd nanosheets within this concentration range.

[0013] Optionally, in step (1), the steady-state fluorescence quenching method includes the following steps:

[0014] (a) Prepare a series of surfactant solutions of varying concentrations in an ethanol-water mixed solvent identical to the final synthesis, and prepare methanol stock solutions of pyrene and benzophenone.

[0015] (b) Take surfactant solutions of various concentrations, add equal amounts of pyrene stock solution to each, and then add different volumes of benzophenone stock solution to one of the sample groups to form a quencher concentration gradient series. All samples are subjected to ultrasonic treatment and then kept at a constant temperature and protected from light to reach equilibrium.

[0016] (c) Using a fluorescence spectrometer, under the conditions of excitation wavelength 335 nm and emission wavelength 373 nm, the fluorescence intensity I of each sample and the intensity I0 of the control sample without quencher were measured.

[0017] (d) Calculate N at each concentration using the Turro-Yekta formula. agg Values, plotting surfactant concentration versus N agg Quantitative relationship graph.

[0018] Optionally, in step (b), the ultrasonic treatment time is 10-30 min, and the ultrasonic treatment power is 100-300W;

[0019] The temperature for constant temperature and light protection equilibrium is 24.5~25.5℃, and the time for constant temperature and light protection equilibrium is 0.8~1.2h.

[0020] Optionally, in step (d), the Turro-Yekta formula is as follows:

[0021]

[0022] Substituting equation (1) into equation (2) yields equation (3), where [Det] is the total concentration of the surfactant solution, [CMC] is the critical micelle concentration, and [Q] is the concentration of the quencher added to the system.

[0023] At 25℃, the conductivity κ of each solution was measured using a conductivity meter. Each sample was measured three times in parallel. The conductivity κ was plotted against the concentration c. The concentration corresponding to the inflection point of the curve is the critical micelle concentration [CMC].

[0024] With [Q] as the x-axis, A linear fit is performed on the ordinate, and its slope is... Therefore, N at each concentration can be calculated. agg Finally, the relationship between surfactant concentration and N was plotted. agg Quantitative relationship graph.

[0025] Optionally, in step (2), all other synthesis conditions include precursor type, precursor concentration, reducing agent type, solvent composition, temperature, ultrasonic power, and ultrasonic time.

[0026] The quantitative characterization of the morphology of the obtained samples includes statistically analyzing the area percentage of nanosheets based on transmission electron microscopy images and / or measuring the average thickness of the nanosheets.

[0027] Optionally, the surfactant comprises hexadecyltrimethylammonium bromide;

[0028] The N agg The effective design range is 69~81, and the corresponding concentration range of hexadecyltrimethylammonium bromide is 120~150 times the critical micelle concentration.

[0029] In this application, based on N agg - The relationship curve of morphology indicators shows that morphology indicators (such as nanosheet yield) change with N. agg The change is not linear, but rather there exists a plateau region. When N agg When the value is in the range of approximately 69 to 81, the area percentage of the two-dimensional nanosheets remains consistently above 90%, and the thickness distribution is relatively uniform; once N... agg When the value is below 69 or above approximately 81, the area ratio of nanosheets decreases sharply, and the uniformity of product morphology deteriorates significantly. This plateau region corresponds to N... agg The value range (69~81) is the "effective design interval of micelle aggregation number" that can be objectively determined through experimental data and can synthesize the target morphology with "stability and high reproducibility". The upper and lower limits of this interval are the critical points where the morphology quality undergoes a qualitative change.

[0030] Optionally, in step (3), the ultrasonic radiation chemical synthesis includes: dissolving the palladium precursor, ascorbic acid and surfactant in an ethanol / water mixed solvent, subjecting the mixture to ultrasonic radiation under inert gas protection, and collecting, washing and drying the product after the reaction is completed.

[0031] In step (3) of this application, the effective design range (N) of micelle aggregation number defined in step (2) is... agg =69~81) is the design starting point for synthesis and the only quantitative input guiding all subsequent process decisions. Based on the surfactant concentration and micelle aggregation number N constructed in step (1), agg By using the quantitative relationship graph, reverse lookup and calculation are performed to determine the N that makes the system... aggThe surfactant concentration value stably falls within the range of 69~81. According to the quantitative correspondence of the spectrum, this concentration range is approximately 0.124 M to 0.155 M (corresponding to approximately 120×[CMC] and 150×[CMC] in this experimental system, respectively). This process realizes the rational transformation from microscopic state target to macroscopic process parameters. This calculation process replaces the traditional trial-and-error mode of "finding" the optimal concentration through a large number of repeated experiments. Within the concentration window (120~150×[CMC]) determined therefrom, the ultrasonic radiation chemical synthesis of Pd nanosheets is performed (e.g., involving common steps such as palladium salt reduction and ultrasonic treatment). The fundamental innovation and decisive difference of this step is that the primary and sufficient reason for selecting the specific CTAB concentration value (whether 120×[CMC], 130×[CMC] or 150×[CMC]) is that the concentration, as verified by the spectrum in step (1), can ensure the micelle N of the reaction system. agg The values ​​fall within the effective design range of 69 to 81. This signifies a shift in synthesis from imitating a "proven and effective isolated concentration point" to a rational application of a "tolerant process parameter window defined by the microscopic state," thereby ensuring the predictability, high reproducibility, and strong universality of the method in principle.

[0032] Optionally, the palladium precursor comprises Pd(NO3)2·2H2O;

[0033] The molar concentration of the ascorbic acid is 2.27 × 10⁻⁶. -3 M;

[0034] The volume percentage of ethanol in the ethanol / water mixed solvent is 20%.

[0035] The inert gas includes nitrogen;

[0036] The ultrasonic radiation treatment lasted for 1-2 hours, with an ultrasonic frequency of 15-25 kHz and an output power of 450-550W.

[0037] The reaction temperature is 13~15°C.

[0038] Secondly, this application provides a defect-controllable two-dimensional Pd nanosheet prepared by the above-mentioned method for quantitatively controlling the preparation of defect-controllable two-dimensional Pd nanosheets based on template state parameters. The defect-controllable two-dimensional Pd nanosheets have an average thickness of 2~4 nm and contain twins and / or stacking fault crystal defects induced by layered micelle templates.

[0039] In this application, the customized structure of the defect-controllable two-dimensional Pd nanosheets enables them to exhibit significantly better performance than catalysts prepared by conventional methods in both methanol oxidation and hydrogen evolution reactions.

[0040] Thirdly, this application provides the application of the aforementioned defect-controllable two-dimensional Pd nanosheets in electrocatalytic methanol oxidation or electrocatalytic hydrogen evolution reaction.

[0041] Compared with the prior art, this application has the following advantages:

[0042] (1) This application provides a quantitative and standardized micelle template characterization and synthesis control process: by introducing a standardized steady-state fluorescence quenching mapping step, the traditionally invisible dynamic behavior of micelles is transformed into a precisely measurable N. agg The value is determined and made into the only quantitative bridge connecting the synthesis conditions and the product morphology, thus completely solving the "cognitive black box" problem.

[0043] (2) This application provides a clear process window based on scientific data, achieving a high degree of reproducibility in the synthesis: the "effective design range of micelle aggregation number" (N) defined in this application agg =69~81)) is a scientific conclusion based on extensive quantitative measurements and morphological correlation analysis. This range represents a stable and tolerant process control window, as long as the N of the synthesis system is ensured. agg If the value falls within this window, it can be guaranteed that palladium nanosheets with consistent morphology and structure can be synthesized in different batches and different laboratories, which perfectly solves the core bottleneck of industrial scale-up.

[0044] (3) This application realizes a fundamental shift from "experience-based trial and error" to "rational design": it establishes a complete rational design paradigm of "quantitative mapping → correlation definition → reverse control". This paradigm is universal and can be extended to other nanomaterial synthesis systems using micelles as templates, transforming materials research and development from an art to a science.

[0045] (4) This application directly leads to the controllable preparation of high-performance catalytic materials: The palladium nanosheets prepared by this method have highly active defect structures that are inevitable products under precise control, thus exhibiting excellent and stable electrocatalytic performance, proving the great practical value of this method in the preparation of cutting-edge functional materials. Attached Figure Description

[0046] To more clearly illustrate the technical solutions of the embodiments of this application, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of this application and should not be regarded as a limitation of the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.

[0047] Figure 1 This is a schematic diagram illustrating the principle and flow of the "quantitative micelle engineering" method of this application.

[0048] Figure 2 This is a graph showing the relationship between CTAB conductivity and concentration in the ethanol / water mixed solvent system (ethanol volume percentage is 20%) of this application.

[0049] Figure 3 For the CTAB concentration-N of this application agg Quantitative relationship graph;

[0050] Figure 4 The images show the TEM and SAED plots (a), dark-field TEM and thickness measurement histogram (b), and compositional characterization plot (c) of sample S4 in this application.

[0051] Figure 5 This is a fine structural characterization image of sample S4 in this application (Note: a represents a TEM image; b represents the HRTEM image of the area within the dashed box in image a; c represents the magnified HRTEM image corresponding to b).

[0052] Figure 6 The TEM and HRTEM images of samples S1(a), S4(b), and S6(c) of this application are shown below (Note: a1 represents the HRTEM image of sample S1; a2 represents the magnified HRTEM image of the area within the red dashed box of a1; b1 represents the HRTEM image of sample S4; b2 represents the magnified HRTEM image of the area within the red dashed box of b1; c1 represents the HRTEM image of sample S6; c2 represents the magnified HRTEM image of the area within the red dashed box of c1).

[0053] Figure 7 The CV curve, chronoamperometry (CA) curve, and electrochemical impedance spectroscopy (EIS) Nyquist plot (ac) of the sample in 1 M KOH + 1 M MeOH; and the Pd mass-normalized CV curve, chronoamperometry (CA) curve, and EIS Nyquist plot (df) of the sample in 1 M KOH + 1 M EtOH.

[0054] Figure 8 For the sample in 0.5 M H2SO4, at 5 mV·s -1 LSV polarization curves at scan rate (a); and at a current density of 10 mA·cm⁻¹ -2 Overpotential plots of all catalysts (b); and Tafel plots of the samples (c). Detailed Implementation

[0055] The present application is further illustrated below with reference to specific embodiments. The following descriptions are merely a few embodiments of the present application and are not intended to limit the present application in any way. Although the present application discloses preferred embodiments as follows, they are not intended to limit the present application. Any modifications or variations made by those skilled in the art without departing from the scope of the technical solution of the present application using the disclosed technical content are equivalent to equivalent implementation cases and all fall within the scope of the technical solution.

[0056] Unless otherwise specified, the raw materials used in the embodiments of this application are all purchased commercially and used directly without any special treatment.

[0057] Unless otherwise specified, the analytical methods in the embodiments all adopt conventional instrument or equipment settings and conventional analytical methods.

[0058] Figure 1 This is a schematic diagram illustrating the principle and flow of the "quantitative micelle engineering" method of this application.

[0059] Example 1

[0060] In this embodiment, CTAB is used as a surfactant to establish the relationship between CTAB concentration and N in the synthesis system. agg Quantitative relationship graph:

[0061] This embodiment aims to establish the relationship between CTAB concentration and N in the synthesis system. agg The quantitative relationship map provides an indispensable initial database for the entire rational design process.

[0062] 1. Standardized Solution Preparation: A series of CTAB solutions with varying concentrations were prepared in an ethanol-water mixture (ethanol comprising 20% ​​by volume) (Table 1). Simultaneously, a precise methanol stock solution of pyrene (concentration: 1.0 × 10⁻⁶) was prepared. -7 M) and methanol stock solution of benzophenone (concentration: 5.0 × 10⁻⁶) -3 M).

[0063] 2. Preparation of Fluorescence Test Samples: Take 5.0 mL of each concentration of CTAB solution and add an equal volume of pyrene stock solution. Then, add different volumes of benzophenone stock solution to one group of samples to form a quencher concentration gradient series ([Q] = 0.0002M, 0.0004M, 0.00048M, 0.00056M, 0.00064M, 0.00072M, 0.0008M, 0.001M, 0.0012M). All samples were ultrasonically treated (40 kHz, 100 W) for 0.5 h and then equilibrated at 25℃ for 1 h.

[0064] 3. Spectral acquisition and data processing: Using an Edinburgh Instruments FLS1000 fluorescence spectrometer, the fluorescence intensity I of each sample and the intensity I0 of the control sample without quencher were measured under the conditions of excitation wavelength 335 nm and emission wavelength 373 nm (i.e., the first vibrational peak of pyrene).

[0065] 4. Aggregate number calculation and spectrum plotting: For each CTAB concentration point, the data is processed according to the Turro-Yekta formula:

[0066]

[0067] Substituting equation (1) into equation (2) yields equation (3), where [Det] is the total concentration of CTAB, and [CMC] is the pre-determined critical micelle concentration, i.e., 1.03 × 10⁻⁶. -3 M (CTAB was prepared into a stock solution of a certain concentration, and diluted with an ethanol / water mixed solvent (ethanol volume ratio of 20%) to obtain CTAB solutions of different concentrations. The conductivity κ of each solution was measured at 25℃ using a conductivity meter. Each sample was measured in triplicate. A graph was plotted between conductivity κ and concentration c. The concentration corresponding to the inflection point of the curve is the critical micelle concentration [CMC]. Figure 2 As shown. By Figure 2 It can be seen that in the low CTAB concentration region, CTAB is expressed as free ion CTA. + and Br - In its current form, the ion concentration in the solution is low, the interaction between ions is weak, and the conductivity increases rapidly with concentration. When the concentration reaches a certain value, CTAB molecules aggregate to form micelles, and some Br... - Ions bind to the surface of the micelles, reducing the number of freely moving ions in the solution and slowing the rate of increase in conductivity. The inflection point on the curve is the CMC of CTAB at a volume fraction of 20% ethanol, which is 1.03 × 10⁻⁶. -3 mol / L);

[0068] With [Q] as the x-axis, A linear fit is performed on the ordinate, and its slope is... Therefore, the micelle aggregation number N at each concentration can be calculated. agg CTAB concentration and N agg The quantitative correspondence is shown in Table 1, which preliminarily predicts the micelle morphology and the morphology and structure of the synthesized nano-Pd materials.

[0069] Table 1. Quantitative Correlation between CTAB Concentration and Micellar Aggregate Number (Nagg)

[0070]

[0071] and Figure 3The "CTAB concentration-N" graph in this embodiment is plotted using the steady-state fluorescence quenching method. agg Quantitative relationship graph (i.e., the graphical representation in Table 1). This graph, in the form of a curve, shows the relationship between CTAB concentration (expressed as CMC multiples) and N. agg The non-linear correspondence between them. N is highlighted in the diagram. agg The effective design range corresponds to the CTAB concentration process window (approximately 120-150 times CMC), and the N concentrations within and outside this window. agg The dramatic changes in the value intuitively reveal the stable existence range of the layered phase. This completes the first step of "quantitative micelle engineering," namely, establishing the key state parameter (N). agg The precise mapping relationship between (concentration) and macroscopic process parameters (concentration).

[0072] Example 2

[0073] Define N agg Effective design range:

[0074] This embodiment aims to investigate the microstate of micelles (N agg The quantitative structure-activity relationship between N and the macroscopic morphology of the final product is used to scientifically define N that can stably guide the target morphology. agg Effective design interval. Series control synthesis: Based on the data from Example 1, six corresponding N values ​​were precisely selected. agg Nano-Pd materials were synthesized at CTAB concentrations of 20.36, 32.17, 69.56, 73.27, 80.83, and 179.78. The synthesis process is as follows: 5.85 × 10⁻⁶ Pd nanoparticles were measured... -4 M Pd(NO3)2·2H2O, 2.27×10 -3 Ascorbic acid (AA) of M and a series of concentrations of CTAB were reacted in a sealed glass container containing a 60 mL ethanol / water mixture (ethanol volume percentage 20%). The reaction temperature was controlled at 14°C, and the mixture was subjected to ultrasonic irradiation for 1.5 h using an ultrasonic cell disruptor (Xianou XO-1800D) equipped with a 20 mm diameter titanium alloy probe. The instrument operated at a frequency of 20 kHz and an output power of 500 W. The entire reaction was protected by nitrogen. The resulting products were collected by centrifugation at 8000 rpm for 30 min, washed sequentially with ultrapure water and ethanol, and finally dried under vacuum at 40°C for 24 h. The corresponding products were dispersed in ethanol and stored, labeled as S1-S6.

[0075] Data Correlation and Interval Definition: Morphological and structural characterization was performed on the six synthesized samples. To quantify the formation of two-dimensional structures, the percentage of area occupied by nanosheets with ultrathin two-dimensional morphologies was statistically analyzed and denoted as the "nanofacial fraction" of the sample. Simultaneously, the thickness of at least 10 nanosheets was measured. Taking S4 as an example, the obtained TEM image of the sample is shown below. Figure 4 As shown, the ultrathin properties of the nanosheets are demonstrated at a field of view of 0.65 μm × 0.66 μm. TEM images show that their surface morphology is smooth (in... Figure 4 (A in the figure is marked with a yellow dashed box). Some nanosheet overlap was observed, stemming from their ultrathin and flexible nature, leading to folding and stacking during sample preparation. The corresponding selected area electron diffraction (SAED) pattern provided in the inset confirms its face-centered cubic (FCC) structure, labeled with {111}, {200}, {220}, {311}, and {222} crystal planes. This labeling indicates a randomly oriented polycrystalline structure. The corresponding high-angle annular dark-field (HAADF) image (… Figure 4 b) in the image further confirms its ultrathin morphology. The dark areas in the image (in...) Figure 4 (The red arrows in ab) can be attributed to the vertical orientation and assembly of the nanosheets on the copper mesh. Energy-dispersive X-ray spectroscopy (EDS) analysis ( Figure 4 c) Confirms that the nanosheets consist solely of Pd. The area occupied by the nanosheets was 96.15%. The average thickness was 3.01 nm. The N content of the six samples was... agg The value is correlated with the area fraction of the nanosheets, and the results are shown in Table 2. Figure 2 "N" agg - Specification of the "morphological association" module.

[0076] Table 2. Number of micelle aggregates (N) agg Correlation data between the product morphology quantification index (nanofacial area ratio) and the product morphology quantification index.

[0077]

[0078] Analysis shows that when N agg When the value is between 69.56 and 80.83 (corresponding to samples S3-S5), the nanosheet area fraction is higher than 90%, and the thickness distribution is relatively uniform; when N agg When the value is below 69.56 (S1, S2) or as high as 179.78 (S7), the nanosheet yield is less than 50%, and the morphology uniformity is poor. Therefore, through objective quantitative data, the effective design range for the micelle aggregation number is approximately N. agg =69~81, the corresponding reliable CTAB concentration process window is approximately 120×[CMC] to 150×[CMC]. Figure 5Here is a fine structural characterization image of sample S4, in which... Figure 5 bc in the text are respectively Figure 5 The magnified image of the area within the yellow dashed box (a) and the corresponding high-resolution TEM image, obtained through "quantitative micelle engineering," demonstrates that the nanostructures obtained are induced by atomic-scale defects such as stacking faults, stepped surfaces, vacancies, lattice distortions, and amorphous boundaries induced by the layered micelle liquid crystal template. This proves that the method can rationally create highly active microstructures.

[0079] TEM and HRTEM analyses of representative samples S1, S4, and S6 showed that ( Figure 6 In N, ac) agg At lower values, CTAB is mainly distributed by sparse spherical micelles. Its weak spatial constraint and minimal interfacial disturbances cannot induce significant lattice distortion in the palladium crystal, allowing palladium atoms to grow slowly and regularly under low stress, forming a crystal structure with high lattice order and extremely low defect density. At N... agg Within the platform window, CTAB micelles form rod-shaped micelles, which, through hydrophobic interactions and electrostatic adsorption, allow Pd atoms to preferentially grow along the two-dimensional direction, forming nanosheet structures. Simultaneously, the interaction between the micelles and the crystal surface generates anisotropic interfacial stress and moderate spatial constraint, leading to uneven growth rates across different crystal planes. This uneven growth further induces lattice mismatches between adjacent crystal planes, thereby inducing the formation of numerous planar defects such as double grain boundaries and stacking dislocations. This results in palladium nanosheets exhibiting high-density double grain boundaries and stacking dislocations, ultimately forming a continuous defect network. The increase in defect density, when N... agg Beyond the plateau window, excessive CTAB causes the micelle aggregates to transform from a layered liquid crystal phase to a random aggregate phase, disrupting the template environment for two-dimensional growth. At this point, the growth of Pd atoms is excessively suppressed, causing the palladium crystal growth to lose its ordered guidance, forming amorphous clumps or broken nanocrystals, failing to form continuous crystal faces and regular defects, resulting in a decrease in defect density.

[0080] Example 3

[0081] Electrocatalytic performance verification:

[0082] The samples used in this embodiment were directly derived from a series of control samples synthesized to define the effective range (i.e., the products synthesized at CTAB concentrations of 30, 130, and 160 times the CMC, respectively, as described in the background art and Example 2, namely S1, S4, and S6). Performance testing and data analysis: Systematic electrochemical tests were performed on the above three self-made samples and commercial Pd / C. The specific test data are shown in Table 3. Figure 7 These are the electrochemical performance test curves of the sample for methanol oxidation (MOR) and ethanol oxidation (EOR). Figure 8 These are the key performance test curves under corresponding acidic conditions. Catalytic performance depends on N.agg Whether the value falls within the valid design range (69-81) defined in this application. The sample within the range (S4) shows significantly better performance in all aspects than the samples outside the range (S1 and S6) and the commercial Pd / C comparative sample. Among them, the best-performing sample, S4, has an electrochemical active area (ECSA) of 37.54 m². 2 g -1 The mass activities for methanol oxidation and ethanol oxidation were 3.278 and 3.031 Amg, respectively. Pd -1 These are approximately 1.31, 21.42, and 14.03 times that of commercially available Pd / C, respectively. From Figure 7 As can be seen from b and e, after a stability test of 3600 Hz, sample S4 maintained the highest steady-state mass activity from 0.01 Hz to 10 Hz. 5 Electrochemical impedance spectroscopy (EIS) was performed in the Hz frequency range to investigate its charge transfer kinetics. Nyquist plots recorded in N2-saturated 1 M KOH solutions containing 1 M methanol or ethanol exhibited characteristic semicircles, the diameter of which was proportional to the charge transfer resistance (Rct). S4 showed the smallest semicircle diameter among the catalysts, indicating the lowest Rct, the most efficient charge transfer, and thus excellent electrocatalytic kinetics. Figure 8 The sample was determined to be in operation at a current density of 10 mA·cm⁻¹. -2 The overpotential at that time was determined. Among them, S4 exhibited the lowest overpotential (95 mV), indicating that it has the best catalytic activity. Furthermore, from LSV data ( Figure 8 c) The Tafel slope was derived to elucidate the kinetic characteristics of the HER process. A lower Tafel slope value implies higher catalytic activity at a lower overpotential. The Tafel slopes of various catalysts are summarized in Table 3. S4 exhibits the lowest Tafel slope (75.15 mV·dec). -1 This highlights its superior HER kinetics under acidic conditions.

[0083] Table 3. Based on micelle aggregation number (N) agg Performance comparison of samples synthesized within the effective range with commercial Pd / C comparative samples.

[0084]

[0085] In summary, the method described in this application, through controlled synthesis within an effective range, produces catalysts (such as the S4 sample) that exhibit performance improvements several times over existing mainstream commercial catalysts (Pd / C) in multiple key electrocatalytic reactions. This fully demonstrates the significant advancement and practical value of this invention in enhancing the functional properties of materials. The examples, based on existing data, prove that the "effective design range for micelle aggregation number (N...)"agg =69~81) is not a theoretical range, but an empirical tool with clear morphological and performance indications. Only by actively controlling the micelle state of the synthesis system within this range can palladium nanosheets with ultrathin two-dimensional morphology and high-density defects be stably and predictably obtained, thereby achieving a qualitative leap in performance. This completely overcomes the shortcomings of existing technologies that rely on single concentration experience and cannot guarantee performance reproducibility. In addition, the method for preparing defect-controllable two-dimensional Pd nanosheets based on template state parameters provided in this application can be widely used in clean energy fields such as electrocatalysis, fuel cells, and water electrolysis for hydrogen production, and is especially suitable for large-scale production scenarios where precise control of the morphology and structure of nanocatalysts is required. The "quantitative micelle engineering" paradigm of this application has universality and can be extended to other nanomaterial systems prepared with surfactant soft templates, and has broad industrial application prospects.

[0086] The above description is merely a few embodiments of this application and is not intended to limit this application in any way. Although this application discloses preferred embodiments as described above, it is not intended to limit this application. Any changes or modifications made by those skilled in the art without departing from the scope of the technical solution of this application using the disclosed technical content are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A method for quantitatively preparing defect-controllable two-dimensional Pd nanosheets based on template state parameters, characterized in that, Includes the following steps: (1) The aggregation number N of micelles formed by different concentrations of surfactant in the synthesis reaction system was determined by steady-state fluorescence quenching method. agg Measurements were performed, and a graph was plotted showing the relationship between surfactant concentration and micelle aggregation number N. agg Quantitative relationship graph; (2) Based on the quantitative relationship spectrum drawn in step (1), select at least 5 characteristic concentration points covering the full concentration range, and synthesize a series of Pd nanomaterial samples in parallel while keeping all other synthesis conditions consistent. Quantitatively characterize the morphology of the obtained samples and determine the N corresponding to each sample. agg The value is correlated with its morphological quantification index, and N is plotted. agg - Morphology index relationship curve, based on which the N-type nanomaterials capable of stably synthesizing two-dimensional Pd nanosheets with the target morphology are determined. agg Effective design range; (3) N determined in step (2) agg The effective design interval is the only control target. Based on the quantitative relationship graph drawn in step (1), reverse search and calculation are performed to determine the N that can be controlled in the system. agg The surfactant concentration range falling within the effective design range is used for the ultrasonic radiation chemical synthesis of Pd nanosheets within this concentration range.

2. The method for quantitatively preparing defect-controllable two-dimensional Pd nanosheets based on template state parameters according to claim 1, characterized in that, In step (1), the steady-state fluorescence quenching method includes the following steps: (a) Prepare a series of surfactant solutions of varying concentrations in an ethanol-water mixed solvent identical to the final synthesis, and prepare methanol stock solutions of pyrene and benzophenone. (b) Take surfactant solutions of various concentrations, add equal amounts of pyrene stock solution to each, and then add different volumes of benzophenone stock solution to one of the sample groups to form a quencher concentration gradient series. All samples are subjected to ultrasonic treatment and then kept at a constant temperature and protected from light to reach equilibrium. (c) Using a fluorescence spectrometer, under the conditions of excitation wavelength 335 nm and emission wavelength 373 nm, the fluorescence intensity I of each sample and the intensity I0 of the control sample without quencher were measured. (d) Calculate N at each concentration using the Turro-Yekta formula. agg Values, plotting surfactant concentration versus N agg Quantitative relationship graph.

3. The method for quantitatively preparing defect-controllable two-dimensional Pd nanosheets based on template state parameters according to claim 2, characterized in that, In step (b), the ultrasonic treatment time is 10-30 min, and the ultrasonic treatment power is 100-300W; The temperature for constant temperature and light protection equilibrium is 24.5~25.5℃, and the time for constant temperature and light protection equilibrium is 0.8~1.2h.

4. The method for quantitatively preparing defect-controllable two-dimensional Pd nanosheets based on template state parameters according to claim 2, characterized in that, In step (d), the Turro-Yekta formula is as follows: Substituting equation (1) into equation (2) yields equation (3), where [Det] is the total concentration of the surfactant solution, [CMC] is the critical micelle concentration, and [Q] is the concentration of the quencher added to the system. At 25℃, the conductivity κ of each solution was measured using a conductivity meter. Each sample was measured three times in parallel. The conductivity κ was plotted against the concentration c. The concentration corresponding to the inflection point of the curve is the critical micelle concentration [CMC]. With [Q] as the x-axis, ln A linear fit is performed on the ordinate, with a slope K= Therefore, N at each concentration can be calculated. agg Finally, the relationship between surfactant concentration and N was plotted. agg Quantitative relationship graph.

5. The method for quantitatively preparing defect-controllable two-dimensional Pd nanosheets based on template state parameters according to claim 1, characterized in that, In step (2), all other synthesis conditions include precursor type, precursor concentration, reducing agent type, solvent composition, temperature, ultrasonic power, and ultrasonic time; The quantitative characterization of the morphology of the obtained samples includes statistically analyzing the area percentage of nanosheets based on transmission electron microscopy images and / or measuring the average thickness of the nanosheets.

6. The method for quantitatively preparing defect-controllable two-dimensional Pd nanosheets based on template state parameters according to claim 1, characterized in that, The surfactant includes hexadecyltrimethylammonium bromide; The N agg The effective design range is 69~81, and the corresponding concentration range of hexadecyltrimethylammonium bromide is 120~150 times the critical micelle concentration.

7. The method for quantitatively preparing defect-controllable two-dimensional Pd nanosheets based on template state parameters according to claim 1, characterized in that, In step (3), the ultrasonic radiation chemical synthesis includes: dissolving palladium precursor, ascorbic acid and surfactant in an ethanol / water mixed solvent, subjecting the mixture to ultrasonic radiation under inert gas protection, and collecting, washing and drying the product after the reaction is completed.

8. The method for quantitatively preparing defect-controllable two-dimensional Pd nanosheets based on template state parameters according to claim 7, characterized in that, The palladium precursor includes Pd(NO3)2·2H2O; The molar concentration of the ascorbic acid is 2.27 × 10⁻⁶. -3 M; The volume percentage of ethanol in the ethanol / water mixed solvent is 20%. The inert gas includes nitrogen; The ultrasonic radiation treatment lasted for 1-2 hours, with an ultrasonic frequency of 15-25 kHz and an output power of 450-550 W. The reaction temperature is 13~15°C.

9. The defect-controllable two-dimensional Pd nanosheets prepared by the method for quantitatively controlling the preparation of defect-controllable two-dimensional Pd nanosheets based on template state parameters as described in any one of claims 1 to 8, characterized in that, The defect-controllable two-dimensional Pd nanosheets have an average thickness of 2-4 nm and contain twins and / or stacking fault crystal defects induced by layered micelle templates.

10. The application of the defect-controllable two-dimensional Pd nanosheets of claim 9 in the electrocatalytic methanol oxidation reaction or the electrocatalytic hydrogen evolution reaction.